2019
DOI: 10.1021/acs.jnatprod.9b00416
|View full text |Cite
|
Sign up to set email alerts
|

Polyketides from Marine-Derived Aspergillus porosus: Challenges and Opportunities for Determining Absolute Configuration

Abstract: Fungal natural products have inspired and enabled countless modern therapeutics. During a survey of the secondary metabolites of endophytic fungi, we found that Aspergillus porosus produces new polyketides with interesting structural features named porosuphenols A−D (1, 2, 3a, and 3b). The structural elucidation of these metabolites was performed with 1D and 2D NMR techniques, Mosher ester analysis, J-based conformational analysis, and isotope exchange studies. The absolute configuration of these compounds was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 57 publications
0
24
0
1
Order By: Relevance
“…Eurotiales are prolific producers of specialized metabolites and hundreds of NRPs and PKs have been isolated from this order, including the antibiotic penicillin (Toghueo and Boyom 2020). Recently, Aspergillus porosus an endophyte isolated from Fucus vesiculosus (brown alga) was found to produce porosuphenols; PKs with antimicrobial activity (Neuhaus et al 2019). Likewise, Tolypocladium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Eurotiales are prolific producers of specialized metabolites and hundreds of NRPs and PKs have been isolated from this order, including the antibiotic penicillin (Toghueo and Boyom 2020). Recently, Aspergillus porosus an endophyte isolated from Fucus vesiculosus (brown alga) was found to produce porosuphenols; PKs with antimicrobial activity (Neuhaus et al 2019). Likewise, Tolypocladium sp.…”
Section: Discussionmentioning
confidence: 99%
“…Ten carbon homocyclic PPs were obtained from microorganisms including fungi, actinomycetes and myxobacteria (Figure 4). Porosuphenols A-C (19)(20)(21) were isolated from a marine-derived Aspergillus porosus [18], and asperolan (22) was isolated from a Garcinia preussii endophytic fungus Aspergillus japonicus [19]. The absolute configuration of 19 was established using NMR data guided conformer searching and electrostatic circular dichroism (ECD) calculations.…”
Section: Carbon Homocyclic Metabolitesmentioning
confidence: 99%
“…The quantitative structure-activity relationship (QSAR) analysis suggested that the terminal hydrophilic functional group as well as an opposing hydrophobic chain would play an important role in MptpB inhibition activities [10]. Another marine-derived fungus A. porosus produced three new PPs porosuphenols A-C (19-21) and a hydrogenated benzopyran derivative porosuphenol D 103 (Figure 14) [18]. Though a series of conformation analysis was adapted to solve the stereochemistry of 19 and 20, the attempts to assign the absolute configuration of 21 and 103 were unsuccessful.…”
Section: Metabolites Containing Hydrogenated Pyran(s)mentioning
confidence: 99%
“…Substituted resorcinol B (245) showed pronounced cytotoxicity against several cell lines, whereas resorcinol A (244) was almost inactive (GI 50 > 50 μM). New polyketidic metabolites, porosulfenols A-D (234, 235, 237a,b) were obtained from the culture liquid of the Aspergillus porosus strain of marine origin [209]. Two latter compounds are in a dynamic equilibrium under ambient conditions (linear 237a and cyclic 237b forms).…”
Section: Other Polyketidesmentioning
confidence: 99%
“…26; the noted fragments are highlighted in red). Separation of toxic fractions of the culture liquid extract of the marine Aspergillus porosus strain [209] led to the release of the known phytotoxin, sphaeropsidin A (401) [272,273], which recently attracted interest as a cytotoxic agent [274]. Interestingly, the second isolated analog, which is very similar in structure to the known aspergiloid E (400) [273], has a significantly lower activity.…”
Section: Terpenoids Steroids and Related Compoundsmentioning
confidence: 99%